Nursing Professional Development's Spirit of Inquiry Focus Areas. Issue 3 (May 2019) - Harper, Mary G.; Warren, Joan I.; Bradley, Dora; Bindon, Susan L.; Maloney, Patsy
Abstract : An Association for Nursing Professional Development (ANPD) task force was charged with redesigning the association's small research grant process. One step in this process included identifying focus areas for the specialty's spirit of inquiry. Using input from a round table discussion with ANPD annual convention attendees, the Journal for Nurses in Professional Development Editorial Board, and the convention evaluation query, 10 spirit of inquiry focus areas were identified that align with the Nursing Professional Development Practice Model.